Selective Recruitment of Presynaptic and Postsynaptic Forms of mGluR-LTD - Sanderson, Thomas M.; Ralph, Liam T.; Amici, Mascia; Ng, Ai Na; Kaang, Bong-Kiun; Zhuo, Min; Kim, Sang Jeong; Georgiou, John; Collingridge, Graham L. (Frontiers in Synaptic Neuroscience, 2022)
In area CA1 of the hippocampus, long-term depression (LTD) can be induced by activating group I metabotropic glutamate receptors (mGluRs), with the selective agonist DHPG. There is evidence that mGluR-LTD can be expressed by either a decrease in the probability of neurotransmitter release (P(r)) or by a change in postsynaptic AMPA receptor number. However, what determines the locus of expression is unknown. We investigated the expression mechanisms of mGluR-LTD using either a low (30 µM) or a high (100 µM) concentration of (RS)-DHPG. We found that 30 µM DHPG generated presynaptic LTD that required the co-activation of NMDA receptors, whereas 100 µM DHPG resulted in postsynaptic LTD that was independent of the activation of NMDA receptors. We found that both forms of LTD occur at the same synapses and that these may constitute the population with the lowest basal P(r). Our results reveal an unexpected complexity to mGluR-mediated synaptic plasticity in the hippocampus.